Facile Hydrothermal Method for Fabrication Seedless ZnO Nanorod/GO Composite on PCB - Sang, Nguyen Xuan; Mai, Nguyen Hoang; Thi Thuy, Pham; Tuan, Nguyen Tri; Tuan, Pham Van; Cuong, Hoang Van (VNU Journal of Science: Mathematics - Physics; Vol 37 No 3DO - 10.25073/2588-1124/vnumap.4618, 2021)
Herein we report a simple method to grow ZnO nanorod/Graphene oxide (GO) array without the initial seed layer on a printed circuit board (PCB) as the substrate based on Galvanic effect. The hydrothermal growing conditions such as temperature and time were investigated by X-ray diffractometry (XRD), Raman scattering, as well as Scanning Electron Microscopy (SEM). It shown that as-prepare ZnO nanorod was grown well-vertically on the substrate. Furthermore, we investigated the photocatalytic activity of synthesized samples which showed the enhanced photodegradation ability in the composite sample.